Respon Pertumbuhan Bibit Karet (Hevea Brasiliensis Muell. Arg.) Dengan Pemberian Kompos Kulit Buah Kopi - Meizi Astri Yolanda; Y. Yulistrani; W. Warnita (Jurnal Riset Perkebunan, 2021)
Coffee rind compost is generated from coffee industry waste which contains enough nutrients and can be used as a mixture of planting media for supporting the growth of plant seedlings.The growth of rubber tree seedlings can be increased by applying compost as a mixture of planting media that can improve soil physical, chemical and biological properties. The objective of this study was to obtain the best dose of coffee rind compost to support the growth of rubber seedlings. The research was conducted in the experimental field of 3rd Campus Andalas University where located in Sungai Kambut Village, Pulau Punjung Sub-district, Dharmasraya District, from September 2019 to March 2020. An experiment was designed by a Completely Randomized Design (CRD) consisted of 5 treatments and 4 replications. The observed variables were shoot height, number of leaves, stem diameter and shoot root ratio. Observed data’s were analyzed by the F test at 5% level, if the F count more than the F table then it is followed by Duncan's New Multiple Range Test (DNMRT) at 5% level significantly. The results showed that the best dose of coffee rind compost to support the growth of plant height, number of leaves, stem diameter and the shoot root ratio of rubber seedlings was 400 g / polybag.